2019
DOI: 10.1590/1678-7757-2018-0779
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanodiamonds on candida albicans adhesion and surface characteristics of PMMA denture base material - an in vitro study

Abstract: Candida albicans is the main causative pathogen of denture stomatitis, which affects many complete denture patients. Objective: To evaluate the effect of different concentrations of nanodiamonds (NDs) added to polymethyl methacrylate (PMMA) denture base material on Candida albicans adhesion as well as on surface roughness and contact angle. Methodology: Acrylic resin specimens sized 10×10×3 mm3 were prepared and divided into four groups (n=30) according to ND concentration (0%, 0.5%, 1%, 1.5% by wt). Surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 43 publications
6
47
0
3
Order By: Relevance
“…Next, to eliminate the solvent, a rotary evaporator under a vacuum was utilized for 30 minutes at 60°C and 150 rpm. In order to obtain the treated ZrO 2 NPs, samples were dried, subjected to 120°C for 2 hours, and then bench-cooled [19][20][21]. e treated ZrO 2 NPs were weighed using an electronic balance (S-234; Denver Instrument, Gottingen, Germany) and incorporated into a heat-polymerized acrylic resin powder and then mixed using a mortar and pestle.…”
Section: Specimen Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, to eliminate the solvent, a rotary evaporator under a vacuum was utilized for 30 minutes at 60°C and 150 rpm. In order to obtain the treated ZrO 2 NPs, samples were dried, subjected to 120°C for 2 hours, and then bench-cooled [19][20][21]. e treated ZrO 2 NPs were weighed using an electronic balance (S-234; Denver Instrument, Gottingen, Germany) and incorporated into a heat-polymerized acrylic resin powder and then mixed using a mortar and pestle.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…Disk-shaped, heat-polymerized acrylic resin specimens with dimensions of 10 × 2 ± 0.1 mm were fabricated following the conventional method and steps for denture base fabrication in accordance with the manufacturer's instructions [16,20,21]. Wax specimens (Vertex Dental B. V., Soesterberg, Netherlands) were obtained using negative molds and then invested in metal flasks (61B Two Flask Compress; Handler Manufacturing) and type III dental stones (Fujirock EP; GC Corporation, Tokyo, Japan).…”
Section: Specimen Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of ill-fitting dentures leads to oral candidiasis and has been associated with denture stomatitis, which affects saliva production and leads to the development of symptoms [ 4 , 18 , 19 , 20 , 21 , 22 ]. Many studies have reported that prosthetic treatment improved the salivary flow rate [ 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is the main material for the fabrication of dentures because of its simple processing technique, relatively low cost of fabrication process, and high aesthetic properties. 1,2 However, despite these satisfying properties, poor mechanical properties including low fatigue resistance and low impact strength should be improved to obtain long-term clinical success. 3,4 Within the 3 years of using prosthesis, the fracture rate of acrylic resin was determined at 68%, especially from the midline of the prosthesis under masticatory forces.…”
Section: Introductionmentioning
confidence: 99%